HONO emission and production determined from airborne measurements over the Southeast U.S. Issue 15 (13th August 2016) - Neuman, J. A.; Trainer, M.; Brown, S. S.; Min, K.‐E.; Nowak, J. B.; Parrish, D. D.; Peischl, J.; Pollack, I. B.; Roberts, J. M.; Ryerson, T. B.; Veres, P. R.
Abstract: The sources and distribution of tropospheric nitrous acid (HONO) were examined using airborne measurements over the Southeast U.S. during the Southeast Nexus Experiment in June and July 2013. HONO was measured once per second using a chemical ionization mass spectrometer on the NOAA WP‐3D aircraft to assess sources that affect HONO abundance throughout the planetary boundary layer (PBL). The aircraft flew at altitudes between 0.12 and 6.4 km above ground level on 18 research flights that were conducted both day and night, sampling emissions from urban and power plant sources that were transported in the PBL. At night, HONO mixing ratios were greatest in plumes from agricultural burning, where they exceeded 4 ppbv and accounted for 2–14% of the reactive nitrogen emitted by the fires. The HONO to carbon monoxide ratio in these plumes from flaming stage fires ranged from 0.13 to 0.52%. Direct HONO emissions from coal‐fired power plants were quantified using measurements at night, when HONO loss by photolysis was absent. These direct emissions were often correlated with total reactive nitrogen with enhancement ratios that ranged from 0 to 0.4%. HONO enhancements in power plant plumes measured during the day were compared with a Lagrangian plume dispersion model, showing that HONO produced solely from the gas phase reaction of OH with NO explained the observations. Outside of recently emitted plumes from known combustion sources, HONO mixing ratios measured several hundred meters above ground level were indistinguishable from zero within the 15 parts per trillion by volume measurement uncertainty. The results reported here do not support the existence of a ubiquitous unknown HONO source that produces significant HONO concentrations in the lower troposphere. Key Points: Large HONO emissions observed from biomass burning, with HONO accounting for 2 to 14% of emitted reactive nitrogen Direct HONO emissions from power plants measured at night ranged from 0 to 0.4% of emitted NOx Within 15 pptv uncertainty, HONO was indistinguishable from zero outside of recently emitted plumes from known combustion sources